Comparative efficacy and safety of pulmonary surfactant delivery strategies in neonatal RDS: a network meta-analysis - Shiyue Liu; Yu Wang; Xingwang Zhu; Feifan Chen; Yuan Shi (BMC Pulmonary Medicine)
Abstract Purpose To compare five pulmonary surfactant (PS) administration strategies for neonates with respiratory distress syndrome (RDS), including intubation-surfactant-extubation (InSurE), thin catheter administration, laryngeal mask airway (LMA), surfactant nebulization (SN), and usual care, with a particular emphasis on the comparison of the LMA and SN with other strategies. Methods We conducted a systematic search of MEDLINE, EMBASE, PUBMED, and Cochrane CENTRAL databases up to November 2023. Two authors independently conducted data extraction, and assessed bias using the Cochrane Risk of Bias Tool. Frequency-based random-effects network meta-analyses were executed. Results A total of 36 trials and 4035 infants were included in the analysis. LMA (OR: 0.20, 95%CI: 0.09 to 0.42) and Less Invasive Surfactant Administration (LISA) (OR: 0.17, 95%CI: 0.09 to 0.32) significantly reduced intubation rates compared to usual care. SN had a higher intubation rate compared to LISA (OR: 3.36, 95%CI: 1.46 to 7.71) and LMA (OR: 2.92, 95%CI: 1.10 to 7.71). LMA had a higher incidence of BPD compared to LISA (OR: 2.59, 95%CI: 1.21 to 5.54). SN ranked second to LISA in preventing BPD and death, but its efficacy decreased after excluding high-risk studies. SN and LMA had the lowest incidence of adverse events during administration.SN had the highest likelihood of secondary administration. Most results were rated as low or very low quality, with findings related to SN significantly impacted by high-risk trials. Conclusions The thin catheter strategy minimized intubation risk and showed a better composite effect in reducing both mortality and BPD incidence. SN and LMA each showed safety and some clinical benefits in the subpopulations where they were studied, but their efficacy needs further validation through high-quality studies. Registration  This study was registered in PROSPERO (CRD42023463756).